Service Quality Gaps in the Provision of Care to Surgical Patients: a Cross-Sectional Study in the Northwest of Iran - Tayyebeh Rezaei; Akram Ghahramanian; Farahnaz Abdullahzaed; Zahra Sheikhalipour; Mohammad Asghari-Jafarabadi; Zeinab Fadaei (Journal of Caring Sciences, 2018)
Introduction: The evaluation of service quality is a key measurement which provides the necessary information for effective decision making and providing high quality care. This study aimed to investigate the factors affecting the service quality gap for the provision of care from the perspective of surgical patients hospitalized in a teaching hospital in the Northwest of Iran in 2015. Methods: In this descriptive cross-sectional study a total of 300 patients and 101 nurses were selected by random sampling method. The data regarding patients’ expectations and perceptions of the quality of healthcare services were collected using the SERVQUAL questionnaire. Also, the nurses’ demographic data were assessed using the demographic data tool. Results: The mean and standard deviation of the patients’ expectations and perceptions of the quality of healthcare services were 66.59)8.52) and 51.81(11.97), respectively. In all dimensions of the quality of healthcare services, the patients’ perceptions were lower than their expectations. The greatest gap was observed in the dimensions of assurance and responsibility and the lowest gap was reported in the domains of reliability and empathy. There were statistically significant relationships between the nurses’ age, work experiences in surgical wards, professional experiences of nurses, patients’ income level and the gap in the quality of healthcare services. Conclusion: Despite great efforts directed at the field, the healthcare system still faces numerous challenges in the provision of high quality healthcare services to the patients. The health system should support low-income people and employ professional and experienced nurses for improving the quality of healthcare services.